PEMILIHAN PENGRAJIN TERBAIK MENGGUNAKAN MULTI-ATTRIBUTE DECISION MAKING (MADM) TECHNIQUE FOR ORDER PREFERENCE BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) (STUDI KASUS : PT. Sinjaraga Santika Sport, Majalengka) - Fizry Listiyani Maulida; Tatik Widiharih; Alan Prahutama (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2015)
The human resources (HR) known as the employess are the successful of the company. PT. Sinjaraga Santika Sport (Triple’S) is a handmade football company by the craftsmen. Most of the craftsmen go to the rice fields on the growing season or the harvest season. So selection of the best craftsmen is needed in order to the production of the football don’t have problems. The selection uses TOPSIS method. TOPSIS is one of method that can be used to solve MADM problem. The steps of TOPSIS method are calculated the normalized decision matrix, determined the weight, calculated the weighted normalized decision matrix, determined the positif-ideal solutions and negatif-ideal solutions, calculated the separation measures, and calculated the preference value. There are 25 craftsmen and six criteria. The criteria are neatness of the ball, accurateness stitching of the ball, number of the ball, accurateness logo of the ball, cleanness of the ball, and defect proportion. The results in this reseach are the best carftsmen has 0,78861 of preference value and the worst craftsmen has 0,16642 of preference value. Preference value by manual calculate equal with preference value by GUI Matlab. Keywords : TOPSIS, MADM, carftsmen